THE INFLUENCE OF LENGTH OF BUSINESS, UNDERSTANDING ACCOUNTING AND BUSINESS SIZE ON THE QUALITY OF FINANCIAL REPORTS (Case Study in Malioboro Area of Yogyakarta) - Vinsensius Engelbertus Lado; Ratri Paramitalaksmi (Jurnal Ekonomi, 2023)
Micro, Small, and Medium-Sized Enterprises (MSME) prepare excellent financial reports that become accurate accounting information for tax reporting, bank credit applications, and economic decisions in business management, such as those regarding pricing and market development. This experiment aims to determine factors that affect the duration of business, comprehension of accounting concepts, and size of the firm in order to assist Micro, Small, and Medium-Sized Enterprises (MSME) in preparing financial reports. All of the MSME actors in the Kota Yogyakarta district served as the research's population. The "Accidental Sampling Technique" was employed for the sampling in this quantitative study. This study used a Likert scale to obtain data from 44 respondents using questionnaires. Regression analysis is the research's analytical method. The findings of this study indicate that the length of the business, the understanding of accounting, and the size of the business all positively impact the quality of the finance report.